Analysis of Law Enforcement Arrangements Against Human Trafficking Practices as Organized Crime: A Legal Certainty Perspective - Tantimin, Tantimin; Hendrawan, Tiara Ananta (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
Basically, the Indonesian State has been actively combating the crime of trafficking in persons based on jurisdiction, but in reality the practice of trafficking in persons is still rampant against the background of various challenges and obstacles originating internally and externally which are directly related to current law enforcement methods. The urgency of eradicating the practice of trafficking in persons as a crime that is currently rampant must be resolved immediately with several strategies such as reconstructing law enforcement towards a more responsive and prioritizing preventive action in the form of prevention and repressive action, namely the protection of victims of trafficking in persons to achieve legal certainty. This research aims to examine the reconstruction of ideal law enforcement in eradicating the practice of human trafficking in order to realize the value of legal certainty. This research uses qualitative analysis with empirical juridical research method elaborated withstatute approach andsociological approach. The results showed that law enforcement has been rigid so that responsive law enforcement is needed in accordance with the needs of the parties concerned between the victim and the perpetrator in order to achieve legal certainty. [Secara umum, Negara Indonesia telah secara aktif memerangi kejahatan perdagangan orang berdasarkan yurisdiksi, namun pada kenyataannya praktik perdagangan orang masih marak terjadi di tengah berbagai tantangan dan hambatan yang berasal dari dalam dan luar negeri, yang secara langsung terkait dengan metode penegakan hukum yang berlaku saat ini. Urgensi memberantas praktik perdagangan orang sebagai kejahatan yang saat ini merajalela harus segera diatasi dengan beberapa strategi, seperti merekonstruksi penegakan hukum menjadi lebih responsif dan memprioritaskan tindakan preventif dalam bentuk pencegahan dan tindakan represif, yaitu perlindungan korban perdagangan orang untuk mencapai kepastian hukum. Penelitian ini bertujuan untuk mengkaji rekonstruksi penegakan hukum yang ideal dalam memberantas praktik perdagangan manusia guna mewujudkan nilai kepastian hukum. Penelitian ini menggunakan analisis kualitatif dengan metode penelitian yuridis empiris yang dikembangkan dengan pendekatan statuta dan pendekatan sosiologis. Hasil penelitian menunjukkan bahwa penegakan hukum telah kaku sehingga diperlukan penegakan hukum yang responsif sesuai dengan kebutuhan pihak-pihak terkait antara korban dan pelaku guna mencapai kepastian hukum.]